An Analysis of Syntactic Development Stage in Language Acquisition Process in Children Aged 3 Years - Dalpah, Dalpah; Azahra, Dimah; Nargis, Nargis (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This research analyzes 3 years old children to pay attention to their way of communicating by answering questions from us as researchers and how Ryuga (the child being observed) communicates with his parents. With the aim of exploring the stages of syntactic development in the development of language acquisition in 3 years old children. This will focus on understanding the sentence structures they use in communicating or speaking such as declarative, interrogative and imperative sentences. By examining these aspects, the research seeks to provide a detailed picture of the syntactic abilities of three years old children. This study used descriptive qualitative method. The results of this research found that Ryuga, who was the object of research, was able to compose meaningful sentences with the correct structure, using pronouns, and his ability to use various types of sentences such as declarative, interrogative and imperative sentences. all of them show good syntactic development in children aged 3 years in speaking. This progress is likely based on imitation and the role of the first language or mother tongue in forming syntactic abilities in Ryuga.